PRELIMINARY EVIDENCE OF GLYCOGEN SYNTHASE KINASE 3 BETA AS A GENETIC DETERMINANT OF POLYCYSTIC OVARY SYNDROME - Goodarzi, Mark O. (2007)
In this study of 352 women with PCOS and 289 controls, haplotypes spanning the gene for glycogen synthase kinase 3β (GSK3B) were constructed based on nine single nucleotide polymorphisms in White and Black subjects separately. In each racial group we observed that a specific, although different, GSK3B haplotype was associated with increased frequency of PCOS, suggesting that GSK3β contributes to the pathophysiology and inherited basis of PCOS.